2018
DOI: 10.1021/acsami.8b11926
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to Wearable Device via Microfluidic Spinning of Robust and Aligned Fluorescent Microfibers

Abstract: Microfluidic spinning technology (MST) has drawn much attention owing to its ideal platform for ordered fluorescent fibers, along with their large-scale manipulation, high efficiency, flexibility, and environment friendliness. Here, we employed the MST to fabricate a series of uniform fluorescent microfibers. By adjusting the microfluidic spinning parameters, the as-prepared microfibers of different diameters are successfully obtained. For more practice, these regular arranged fibers could be formed to versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…In the authors' research, all three curves had strong emissions at approximately 430 nm at different levels. H-3 and H-5 fibers also showed the highest intensity at approximately 530 nm, illustrating that the result was the same as the spectra measured in the current study, verifying the fluorescent agent prepared in this study was ZnS:Cu fluorescent (Cui et al 2018). It is worth noting that, in the location of 530 nm, the emission intensity tended to increase distinctly upon the increase of fluorescent, which suggests that the intensity at this wavelength was positively correlated with the concentration of fluorescent.…”
Section: Fluorescence Spectra Analysissupporting
confidence: 88%
“…In the authors' research, all three curves had strong emissions at approximately 430 nm at different levels. H-3 and H-5 fibers also showed the highest intensity at approximately 530 nm, illustrating that the result was the same as the spectra measured in the current study, verifying the fluorescent agent prepared in this study was ZnS:Cu fluorescent (Cui et al 2018). It is worth noting that, in the location of 530 nm, the emission intensity tended to increase distinctly upon the increase of fluorescent, which suggests that the intensity at this wavelength was positively correlated with the concentration of fluorescent.…”
Section: Fluorescence Spectra Analysissupporting
confidence: 88%
“…More recently, an alternative microfluidic spinning technology (MST) is emerged to provide an ideal strategy for facile fabrication of aligned microfibers. [35][36][37][38][39][40] In addition, more complicated and interesting structures, including string-of-beads [41] and Janus fibers, [42][43] can be easily manipulated by adjusting the geometric features of the microfluidic channels. For example, Kong et al reported spindle-knot microfibers with cavity knots for large-scale water collection by a gas-in-water microfluidic system.…”
Section: Robust Nanofiber Films Prepared By Electro-microfluidic Spinmentioning
confidence: 99%
“…[45] Our group employed MST to construct various aligned fluorescent fibers for ordered array coding, multidimensional microarrays microreactor and flexible fiber supercapacitor with high energy density. [34,38,41] Still, to realize nanoscale fibers preparation via MST system is a challenge due to the mechanical traction force limitation. Also, the mechanical properties of fibers are still less than satisfactory.…”
Section: Robust Nanofiber Films Prepared By Electro-microfluidic Spinmentioning
confidence: 99%
“…In recent years, some researches demonstrated composite nanofiber using the microfluidic approach. [ 123,124 ] Fundamentally, this type of spinning relies on the microfluidic technology for manipulation of fluid flow in microchannel, as shown in Figure 2b. Ma et al.…”
Section: Fabrication Of Fiber‐shaped Halide Perovskite Composites Andmentioning
confidence: 99%